1974
DOI: 10.1039/c39740000555
|View full text |Cite
|
Sign up to set email alerts
|

Fluoro[imidobis(sulphuryl fluoride)]xenon. An example of a xenon–nitrogen bond

Abstract: The reaction of xenon difluoride with imidobis-(sulphuryl fluoride) in dichlorodifluoromethane at 0" yields the new compound, fluoro [imidobis(sulphuryl fluoride)]xenon, FXeN(SO,F),, the first example of xenon bonded to an element other than oxygen or fluorine under ordinary laboratory conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

1975
1975
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…ÀNb onds occur for trigonal planar (sp 2 -hybridized) inorganic nitrogen ligandsd erived from the (FO 2 S) 2 N( imidobis(sulfurylfluoride)) group, that include FXeN(SO 2 F) 2 , [15][16][17] + , [19] the related (CF 3 O 2 S) 2 N( imidobis(sulfuryltrifluoromethyl)) group, which is solely represented by (Xe[N-(SO 2 CF 3 ) 2 ] 2 ), [20] and the sulfur-nitrogen-fluorine cations derived from NSF 3 ,n amely, [ F 4 S=NXe] + [21] and [F 4 S=NXe···NSF 3 ] + . [22] The only examples in which xenon is bonded to sp 3 -hybridized nitrogen are [F 5 Te N(H)Xe]…”
Section: IImentioning
confidence: 99%
“…ÀNb onds occur for trigonal planar (sp 2 -hybridized) inorganic nitrogen ligandsd erived from the (FO 2 S) 2 N( imidobis(sulfurylfluoride)) group, that include FXeN(SO 2 F) 2 , [15][16][17] + , [19] the related (CF 3 O 2 S) 2 N( imidobis(sulfuryltrifluoromethyl)) group, which is solely represented by (Xe[N-(SO 2 CF 3 ) 2 ] 2 ), [20] and the sulfur-nitrogen-fluorine cations derived from NSF 3 ,n amely, [ F 4 S=NXe] + [21] and [F 4 S=NXe···NSF 3 ] + . [22] The only examples in which xenon is bonded to sp 3 -hybridized nitrogen are [F 5 Te N(H)Xe]…”
Section: IImentioning
confidence: 99%
“…The polymers which were developed are known as perfluorosulfonimide ionomers or PFSI (Fig. 1) and evolved from small molecule work on perfluoroalkylsulfonyl derivatives to form carbon and nitrogen xenon bonds [15,16]. Beginning in the late 1970s, numerous Brfnsted nitrogen superacids were synthesized and are known as bis((perfluoroalkyl)sulfonyl)imides [17].…”
Section: Introductionmentioning
confidence: 99%
“…The first xenon-nitrogen bond in FXeN͑SO 2 F͒ 2 was reported in 1974 by DesMarteau and LeBlond and up to date this and a few similar compounds seem to be the only examples of Xe-N bonding. [3][4][5][6] In 1979, Turbini et al 7 reported the synthesis of Xe͑CF 3 ͒ 2 with a xenon-carbon bond but its unequivocal spectroscopic characterization is still lacking. During the last few years, a number of compounds with Xe-C bonds have been synthesized and characterized, including ionic compounds (C 6 F 5 Xe) ϩ (C 6 F 5 BF 3 )…”
Section: Introductionmentioning
confidence: 99%